Agility Model of Empowerment for Village-Owned Enterprises (BUMDes) in Indonesia - Akbar, Gugun Geusan; Karmila, Mila (GoAcademica Research & Publishing, 2024)
This article explores the concept of agility in the context of empowering Village-Owned Enterprises (BUMDes) in Indonesia. Facing complex challenges in a dynamic environment, BUMDes requires a more adaptive and responsive approach to enhance its performance. Through a dynamic systems approach, this article identifies key factors influencing BUMDes agility, including human resource capacity, technology adoption, collaboration, and local government support. Furthermore, the article emphasizes the importance of operational transparency, oversight, strategic planning, and human resource development as core processes in achieving agility. The outcomes of this process include improved BUMDes performance, increased revenue, and a positive impact on community empowerment. By implementing the proposed model, BUMDes can be more responsive to changes, improve its performance, and contribute more effectively to village development. This article provides valuable insights for policymakers, practitioners, and researchers interested in BUMDes empowerment and organizational agility.